PELESTARIAN GEGURITANMELALUI RADIO AMATIR PADA PESANTIAN DIRGAHAYU AMBARA SWARI BALI - Wirata, I Gede Dharma; Kebayantini, Ni Luh Nyoman; Sastri Mahadewi, Ni Made Anggita (JURNAL ILMIAH SOSIOLOGI: SOROT, 2019)
ABSTRACT This study discusses in descriptive explanative manners the preservation of Balinese literature that occurred in amateur radio PesantianDirgahayuAmbaraSwari. Balinese literature specifically discussed this as geguritan. Geguritan is a simple literary form of language structure, and standard rules (padalingsa). The research of literary sociology from Robert Escaprit is ideal for the identity of Balinese society through literary culture communicated via amateur radio in Bali area network. Efforts to preserve geguritan arise because of the cultural dominance outside due to globalization in Balinese society.Through this research, geguritanSudamalaBanaspati Raja version 3 will be discussed with Robert Escarpit's analysis of accepting the ideal ideas from literary writers which contain interpretationsin society.The meaning of geguritanSudamalaBanaspati Raja version 3 is needed, including the meaning of balinization, spiritual meaning, and the meaning of the organization involving the geguritan among the community. Keywords: Preservation, Geguritan, Amateur Radio, Pesantian Dirgahayu Ambara Swari.